A Systematic Literature Review: Efektivitas Game Digital terhadap Hasil Belajar Bahasa Indonesia Siswa Sekolah Dasar: - - Rohman Sujarwo, Fathur; Haryadi, Haryadi; Santoso, Bernadus Wahyudi Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has encouraged innovation in Indonesian language learning in elementary schools through the use of digital games. This study used the Systematic Literature Review (SLR) method based on PRISMA to review eight studies published between 2021 and 2025. By searching Google Scholar, we obtained a final analysis of eight relevant articles. The analysis results show that media such as Wordwall, Kahoot, DORA, and Rumah Adiksimba are effective in increasing student motivation and learning outcomes. Supporting factors include attractive design, student engagement, and teacher support, while the constraints are limited facilities and learning time. Overall, game-based learning has been proven effective in improving Indonesian language comprehension in elementary schools. Further research is recommended to develop AI-based adaptive games for more personalized and sustainable learning.